การพยากรณ์ผลผลิตและราคาสินค้าเกษตร - มนฤดี เกิดสมบุญ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This research is a study of forecasting planted areas, products, and farm prices in cases of rice (major and second rice), maize, mungbean, and soybean. The objective of the research is to find an appropriate statistical method of forecasting planted areas, products and farm prices for the aforesaid by the use of forecasting techniques : regression analysis, box-jenkins, exponential smoothing, autoregressive and classical time series analysis. The forecast values of those methods will be compared with the forecast values of the method of the center of agricultural information. To achieve the result, the mean absolute percentage error (MAPE) was used as the criterion for choosing the said six forecasting techniques. This research used second data, complied from the center of agricultural information, the Department of Business Economics, the Office of the National Economic and Social Development Board, the Nation Statistics Office, and the Royal Irrigation Department. The comparison of forecast values from the six techniques by MAPE showed that regression model was suitable for planted areas of major rice, second rice, and mungbean; products of major rice, second rice, maize, and soybean; and farm price of maize (moisture<14%). Box-jenkins model was suitable for farm price of major rice glutinous paddy 5% and soybean (mixed). Autoregressive model was suitable for planted areas of maize and soybean; products of mungbean; and farm price of second rice non-flutinous paddy moisture 14-15%. Classical time series model was suitable for farm price of mungbean shinny large (mixed). Then, the said models were used to forecast planted areas and products for the period of four years, 1997-2000, and farm price for the period of two years, 1999-2000. The result of forecasting were as follows; Major rice: In 2000, planted area trends to decrease from 1999 about 1.12%; product and farm price of major rice glutinous paddy 5% trend to increase from 1999 about 0.74% and 3.55%, respectively. Second rice: In 2000, planted area, product, and farm price of second rice non-glutinous paddy moisture 14-15% trend to decrease from 1999 about 5.61%, 0.68%, and 13.67%, respectively. Maize: In 2000, planted area and product trend to decrease from 1999 about 1.17% and 56.47%, respectively, and farm price of maize (moisture<14%) trends to increase from 1999 about 1.31%. Mungbean: In 2000, planted area and product trend to decrease from 1999 about 0.19% and 14.77%, respectively, and farm price of mungbean shinny large (mixed) trends to increase from 1999 about 0.63%. Soybean: In 2000, planted area and product trend to decrease from 1999 about 28.30% and 35.79%, respectively, and farm price of soybean (mixed) trends to increase from 1999 about 0.10%. According to the above results, the government should ensure that the appropriate meansure for the next year productive situation, and policy responded to decreasing trend of production and price, are seriously considered in order to avoid people and agricultueists difficulties.